CSR Strategy of PT Bank Rakyat Indonesia (BRI) in Supporting the Indonesia ASRI Movement Program in Kedonganan Village, Badung, Bali - Gan Gan Giantika; Siti Qonaah (Jurnal Multidisiplin Sahombu, 2026)
Bali serves as a barometer that reflects Indonesia’s overall condition, particularly in terms of environmental quality and tourism, including the issue of plastic waste. For nearly two decades, Kuta Beach has functioned as a visible showcase of seasonal marine debris accumulation along the coastline. Oceanographic modeling research conducted at nearly 50 observation points across Bali in 2017, 2019, and 2020 produced relatively consistent findings. Using the CSIRO method, plastic waste is categorized into two types, namely fragmented and intact waste. The Indonesia ASRI Movement is a strategic national program initiated during the administration of President Prabowo Subianto, aiming to improve the quality of life of the community. In this context, PT Bank Rakyat Indonesia (BRI) implements its Corporate Social Responsibility (CSR) strategy to support the Indonesia ASRI Movement in Kedonganan Village, Badung, Bali. This study employs a qualitative methodology with a case study approach. Data collection techniques include observation, documentation, and literature review. The CSR strategy implemented by PT BRI in supporting the Indonesia ASRI Movement in Kedonganan Village involves beach clean-up activities aimed at promoting environmental sustainability. Hundreds of volunteers, consisting of BRI employees and local community members, actively participated in waste collection efforts along the Kedonganan Beach area, covering approximately 8,250 m². Through this initiative, BRI Peduli successfully collected 931.16 kg of inorganic waste, with a potential reduction of CO₂ emissions amounting to 2.19 tons. The CSR strategy of PT BRI in supporting the Indonesia ASRI Movement through sustainable beach clean-up initiatives has demonstrably generated positive impacts across multiple dimensions, including social, economic, and environmental aspects within the community.